Cable loss performance investigation of cable-stayed bridge equipped with Roll-N-Cage isolator. (July 2022) - Omran, Mohammad E.; Karani, Abbas H.
Abstract: The cable loss failure, especially during earthquakes, could be a threat to the stability of cable-stayed bridges. In this regard, the purpose of this paper is to study the performance of isolated cable-stayed bridges in case of cable loss conditions. So, Bill Emerson Cable-Stayed Bridge with Roll-N-Cage (RNC) isolators was studied under three seismic events in two cases of (1) intact bridge model (2) bridge model with removed cable. The buffer mechanism of the RNC isolator and its effects on the seismic performance of the bridge were studied considering the time history dynamic analysis using the software of Opensees. The results indicated that the RNC isolator with an activated buffer mechanism appropriately decreases the permanent displacement under seismic loads. In the most critical case, cable loss of one connected the end of the deck to the top of the tower, collapse incidence was prevented by considering the buffer mechanism. RNC isolator with activated buffer mechanism provided the structural stability by forming permanent hysteretic cycles with proper strength and damping energy.